The Evolution of Morality - Shackelford, Todd K.; Hansen, Ranald D. (Evolutionary Psychology, 2016)
This interdisciplinary collection presents novel theories, includes provocative re-workings of longstanding arguments, and offers a healthy cross-pollination of ideas to the morality literature. Structures, functions, and content of morality are reconsidered as cultural, religious, and political components are added to the standard biological/environmental mix. Innovative concepts such as the Periodic Table of Ethics and evidence for morality in non-human species illuminate areas for further discussion and research. And some of the book's contributors question premises we hold dear, such as morality as a product of reason, the existence of moral truths, and the motto "life is good."  Highlights of the coverage:  The tripartite theory of Machiavellian morality: judgment, influence, and conscience as distinct moral adaptations. Prosocial morality from a biological, cultural, and developmental perspective. The containment problem and the evolutionary debunking of morality. A comparative perspective on the evolution of moral behavior. A moral guide to depravity: religiously-motivated violence and sexual selection. Game theory and the strategic logic of moral intuitions. The Evolution of Morality makes a stimulating supplementary text for advanced undergraduate and graduate courses in the evolutionary sciences, particularly in psychology, biology, anthropology, sociology, political science, religious studies, and philosophy.